2018
DOI: 10.1128/jvi.00803-18
|View full text |Cite
|
Sign up to set email alerts
|

A Kaposi's Sarcoma-Associated Herpesvirus Infection Mechanism Is Independent of Integrins α3β1, αVβ3, and αVβ5

Abstract: Host receptor usage by Kaposi's sarcoma-associated herpesvirus (KSHV) has been best studied using primary microvascular endothelial and fibroblast cells, although the virus infects a wide variety of cell types in culture and in natural infections. In these two infection models, KSHV adheres to the cell though heparan sulfate (HS) binding and then interacts with a complex of EphA2, xCT, and integrins α3β1, αVβ3, and αVβ5 to catalyze viral entry. We dissected this receptor complex at the genetic level with CRISP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 72 publications
1
22
0
Order By: Relevance
“…cellular receptor EphA2 for KSHV entry into various adherent target cells (2)(3)(4)(5). While the KSHV gH/gL complex exhibits the highest avidity for EphA2, it can also interact with other members of the Eph family of receptor tyrosine kinases (Ephs), similar to the gH/gL complex of the related rhesus monkey rhadinovirus (RRV) (6).…”
mentioning
confidence: 99%
“…cellular receptor EphA2 for KSHV entry into various adherent target cells (2)(3)(4)(5). While the KSHV gH/gL complex exhibits the highest avidity for EphA2, it can also interact with other members of the Eph family of receptor tyrosine kinases (Ephs), similar to the gH/gL complex of the related rhesus monkey rhadinovirus (RRV) (6).…”
mentioning
confidence: 99%
“…However, redundant functions among the receptors involved may hinder this approach. For example, although integrins such as ␣3␤1, ␣V␤3, or ␣V␤5 are presumed to play a crucial role in KSHV infection (13), they were recently proven to be dispensable for epithelial cell infection (60), suggesting that they may not be ideal targets in a clinical setting. Similarly, a recent study identified conserved residues in the N-terminal domain of gH that mediate EphA2 binding (63).…”
Section: Discussionmentioning
confidence: 99%
“…The epithelial cell-tropism complex gH/gL binds to the ligand-binding domain of EphA2 similar to KSHV (Chen et al, 2018. Interestingly, EBV enters epithelial cells by direct fusion with the plasma membrane, whereas KSHV enters its host cells via an endocytosis pathway involving gH/gL-binding to EphA2, A4 or A5 (Chen et al, 2018, Miller and Hutt-Fletcher, 1992, Chakraborty et al, 2012a, Hahn et al, 2012, Chandran, 2010, Chen et al, 2019, TerBush et al, 2018. EBV gH/gL acts as tropism switch by either interacting with gp42 that facilitates B cell receptor binding or directly binding to the epithelial cell receptor EphA2 (Borza and Hutt-Fletcher, 2002, Matsuura et al, 2010, Möhl et al, 2016.…”
Section: Ebv-driven Entry and Fusionmentioning
confidence: 99%
“…Previous studies demonstrated that several integrins such as αVβ3, αVβ5 and α3β1 are important for infection of human epithelial and endothelial cells as well as esophageal fibroblasts (Akula et al, 2002, Chandran, 2010, Damania and Cesarman, 2013. More recent studies suggest that KSHV infection of epithelial cells is independent of αν-and β1-family integrin expression (TerBush et al, 2018), but requires HSPGs and either EphA2, EphA4, or EphA5 (Chakraborty et al, 2012a, Chandran, 2010, Chen et al, 2019, Damania and Cesarman, 2013, Hahn et al, 2012, TerBush et al, 2018. Interestingly, EphA7 has recently been found to be a receptor required for KSHV entry into B cells (Grosskopf et al, 2019).…”
Section: Kshv-driven Entry and Fusionmentioning
confidence: 99%